im really bad need help!
here you don't have like terms I suggest distributing then combining like terms
and what I mean by you don't have like terms is that x+y is not the same as x-y both terms have different variable parts as is
use the rule I mentioned on your earlier post
will u please give me the answer.. D: i will fan and medal
hint: A(B+C) = A*B + A*C a(x+y) = ????
\[a(x+y) - a(x-y) \implies ax +ay -ax +ay\] combine the like terms
like terms are the variables that are raised to the same power
after combining like terms you get d 2ax-2ay
\[ax + ay - ax + ay\] \[(ax - ax) \implies ? \] \[(ay + ay) \implies ? \]
did you find your answer?